Comparative analysis of male and female populations on prevalence and antibiotic resistance of Mycoplasma hominis in China, 2005–2014. (September 2016) - Kong, Yingying; Qiao, Yingli; Song, Jingjuan; Ruan, Zhi; Fei, Chunrong; Huang, Jun; Song, Tiejun; Jin, Hong; Ding, Honghui; Xie, Xinyou; Zhang, Jun
Highlights: Both single identification of Mycoplasma hominis and simultaneous identification with Ureaplasma spp. were more frequent in females than males. Resistance rates to ofloxacin showed significant differences between the two sexes. Doxycycline, pristinamycin, tetracycline and josamycin are considered to be the primary choice for treating M. hominis infections. Abstract: The aim of this study was to estimate the prevalence and antimicrobial resistance rate of Mycoplasma hominis among male and female populations. A total of 67 921 individuals were examined. All samples were isolated from patients at an outpatient clinic from January 2005 to December 2014. Species identification and antibiotic susceptibility testing were performed using Mycoplasma IST2. In this study, 523 (0.8%) and 4625 (6.8%) cultures, respectively, were positive for single M. hominis identification and simultaneous identification of both M. hominis and Ureaplasma spp. The results showed that both single and simultaneous identification were more frequent in the female than the male population. Moreover, the highest positive rates of single M. hominis identification were observed in 56–60-year-old males and 61–65-year-old females, and the rates of simultaneous identification were high in males aged >65 years and females aged 15–20 years. Among the seven antibiotics assessed, tetracycline, josamycin, doxycycline and pristinamycin were the most effective, whilst clarithromycin, ciprofloxacin and ofloxacin displayed extremely high resistance rates. Different antimicrobial susceptibility rates were observed between the two sexes, and the resistance rates to ofloxacin showed a significant difference ( P  < 0.05). In conclusion, this study demonstrates that the prevalence of M. hominis varied significantly between the two sexes in the past 10 years and that the optimal antimicrobial therapy strategy should be directed by local susceptibility testing.